Principal Planning in Evaluation of Education Programs at SMPIT Nurul Ilmi - Inom Nasution; Nanda Putri Khafifah; Mutiara Hasni; Tri Fatimah; Yuda Mulia Ramadhan Sitepu (Edumaspul: Jurnal Pendidikan, 2022)
Evaluation of educational programs is an activity that must be carried out in every educational institution, this is done so that every educational institution can improve and develop a predetermined planning process, especially in educational programs. In this study, we will discuss the evaluation of educational programs carried out at SMP IT Nurul Ilmi. The research methodology carried out in this study used descriptive qualitative research methods, namely describing the results of research findings in the form of observations and interviews. The results of the research process said that the evaluation of the education program carried out at SMP IT Nurul Ilmi went well because before carrying out the evaluation process for the education program at SMP IT Nurul Ilmi carried out a planning process with the principal and teachers so that in the process of implementing the evaluation of the education program running well. So in conclusion, the evaluation of educational programs conducted at SMP IT Nurul Ilmi runs according to predetermined procedures by carrying out the planning process and predetermined regulations.